2021
DOI: 10.7554/elife.62147
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinase-9 in neurodevelopmental deficits and experience-dependent plasticity in Xenopus laevis

Abstract: Matrix metalloproteinase-9 (MMP-9) is a secreted endopeptidase targeting extracellular matrix proteins, creating permissive environments for neuronal development and plasticity. Developmental dysregulation of MMP-9 may also lead to neurodevelopmental disorders (ND). Here we test the hypothesis that chronically elevated MMP-9 activity during early neurodevelopment is responsible for neural circuit hyperconnectivity observed in Xenopus tadpoles after early exposure to valproic acid (VPA), a known teratogen assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…The decreased synthesis of NCAM in response to neuronal activity supports a model in which transsynaptic complexes are disrupted during seizures and that adhesion molecules could be cleaved by extracellular proteases, contributing to epileptogenesis ( Gorlewicz and Kaczmarek, 2018 ). Indeed, we have recently shown that activity-dependent increased levels of the extracellular metalloprotease, MMP9, which targets the extracellular matrix (ECM) and enhances synaptic plasticity ( Kaliszewska et al, 2012 ), are required for experience-dependent structural and functional visual circuit neuronal development ( Gore et al, 2021 ). These examples show how activity-dependent increases and decreases in NSPs contribute to a unified biological outcome regarding modifications of the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased synthesis of NCAM in response to neuronal activity supports a model in which transsynaptic complexes are disrupted during seizures and that adhesion molecules could be cleaved by extracellular proteases, contributing to epileptogenesis ( Gorlewicz and Kaczmarek, 2018 ). Indeed, we have recently shown that activity-dependent increased levels of the extracellular metalloprotease, MMP9, which targets the extracellular matrix (ECM) and enhances synaptic plasticity ( Kaliszewska et al, 2012 ), are required for experience-dependent structural and functional visual circuit neuronal development ( Gore et al, 2021 ). These examples show how activity-dependent increases and decreases in NSPs contribute to a unified biological outcome regarding modifications of the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 has been implicated as a molecular switch (via proBDNF-to-mBDNF cleavage) to convert axon pruning to stabilization in the Xenopus NMJ and synaptic weakening to strengthening in rodents [30,31,67]. In the Xenopus optic tectum, MMP-9 is necessary for the visual experience driven increase in tectal neuron dendritic growth [68]. It is also plausible that the mode of BDNF release varies during asynchronous and synchronous stimulation, in line with reports proposing that tonic versus acute release of BDNF may differentially regulate the cell surface level of TrkB and thus distinctly affect neurite outgrowth [69][70][71].…”
Section: Molecular Mechanisms Of Axonal "Competition" In the Optic Te...mentioning
confidence: 99%
“…Work of this nature is being complemented by the historic strengths of the Xenopus model, e.g. by using techniques to record neuronal plasticity and action potentials both within intact tadpoles, and in primary cultures of neuronal cells or neuronal/muscle co-cultures derived from embryos with gene variants ( Sun and Poo, 1985 ; Gore et al, 2021 ; Hiramoto and Cline, 2021 ).…”
Section: Introductionmentioning
confidence: 99%